Australian consensus recommendations for the management of hepatitis B. Issue 9 (6th March 2022) - Lubel, John S; Strasser, Simone I; Thompson, Alexander J; Cowie, Benjamin C; MacLachlan, Jennifer; Allard, Nicole L; Holmes, Jacinta; Kemp, William W; Majumdar, Avik; Iser, David; Howell, Jess; Matthews, Gail V
Abstract: Introduction: The prevalence of hepatitis B virus (HBV) infection in Australia is nearly 1%. In certain well defined groups the prevalence is far greater, yet an estimated 27% of people living with HBV infection remain undiagnosed. Appropriate screening improves detection, increases opportunity for treatment, and ultimately reduces the significant morbidity and mortality associated with the development of liver fibrosis and hepatocellular carcinoma (HCC). Main recommendations: This statement highlights important aspects of HBV infection management in Australia. There have been recent changes in nomenclature and understanding of natural history, as well as a newly defined upper limit of normal for liver tests that determine phase classification and threshold for antiviral treatment. As the main burden of hepatitis B in Australia is within migrant and Indigenous communities, early identification and management of people living with hepatitis B is essential to prevent adverse outcomes including liver cancer and cirrhosis. Change in management as a result of this guideline: These recommendations aim to raise awareness of the current management of hepatitis B in Australia. Critically, the timely identification of individuals living with hepatitis B, and where appropriate, commencement of antiviral therapy, can prevent the development of cirrhosis, HCC and mother‐to‐child transmission as well as hepatitis B reactivation in immunocompromised individuals. Recognising patient and viral factors that predispose to the development of cirrhosis and HCC will enable clinicians to risk‐stratify and appropriately implement surveillance strategies to prevent these complications of hepatitis B.